A reestruturação do PPC do curso de Pedagogia do campus de Abaetetuba: o currículo em questão - SILVA, Edina Cristina Silva e (2019)
The present study questions the restructuring process of the Pedagogy course of the Federal University of Pará-Campus / Abaetetuba. The objective of this study is to follow the historical trajectory of restructuring of the PPC of the Pedagogy course of UFPA Campus-Abaetetuba, having as legal framework the LDB and the DCNS / 2015. The methodology used for the construction of this work is the documentary analysis in official documents and the bibliographical research of qualitative character, in scientific articles, following authors such as: Libano (1999, 2000, 2001, 2004, 2005, (2008), Sacristan (2001), Apple (2008), Saviani (2007,2008), Golden (2015), Moreira (2009), Lopes (2016), Mascarenhas. The results indicate that the restructuring of the PPC of the course in question has been carried out since 2007, seeking to form Pedagogues and Critical Pedagogues; currently, the restructuring of the PPC of the Pedagogy course, demands attention the cultural demands of the contemporaneity; on the other hand, the course of Pedagogy and teachers are suffering attacks that constitute a setback in national education.